Autoimmune pemphigus: difficulties in diagnosis and the molecular mechanisms underlying the disease - Simionescu, Olga; Tudorache, Sorin Ioan (Frontiers in Immunology, 2025)
Recently recognised as a desmosomal disorder, autoimmune pemphigus remains severe in some of its forms, such as pemphigus vulgaris. This review is divided into four parts. “Cellular and molecular mechanisms in autoimmune pemphigus” discusses in detail antigenic targets, antibodies, immunological and genetic mechanisms of apoptosis and the involvement of cells and organelles (keratinocytes, lymphocytes, eosinophils and neutrophils) in different forms of pemphigus. These advances have led to today’s first-line biologic therapy for pemphigus. The section “Specific features in the diagnosis of immune pemphigus” deals with the clinical diagnostic clues (enanthema, intertrigo, pruritus, distribution of lesions). The third section, “Characteristics and challenges in different types of pemphigus”, focuses on the importance of using standardised diagnostic criteria in paraneoplastic pemphigus and pemphigus herpetiformis, the specific and difficult situations of differentiation between bullous lupus and autoimmune Senear-Usher pemphigus, between IgA forms of pemphigus or differentiation with other autoimmune diseases or neutrophilic dermatoses. The possibility of subtype cross-reactivity in pemphigus is also discussed, as is the diagnosis and course of the disease in pregnant women. The final section is an update of the “gold standard for the diagnosis and evaluation of autoimmune pemphigus”, the role and place of direct immunofluorescence and additional serological tests. This revision is the first to combine the difficulties in clinical diagnosis with new molecular insights. It provides a comprehensive overview of recent advances in the understanding of autoimmune pemphigus, bridging the clinical challenges and complexities of diagnosing different forms of pemphigus, and is a valuable resource for clinicians caring for patients with pemphigus.